E‐Cadherin restricts mast cell degranulation in mice. Issue 1 (20th October 2021) - Klewer, Theres; Bakic, Ljubica; Müller‐Reichert, Thomas; Kiewisz, Robert; Jessberger, Gregor; Kiessling, Nadine; Roers, Axel; Jessberger, Rolf
Abstract: Crosslinking of FcεRI‐bound IgE triggers the release of a large number of biologically active, potentially anaphylactic compounds by mast cells. FcεRI activation ought to be well‐controlled to restrict adverse activation. As mast cells are embedded in tissues, adhesion molecules may contribute to limiting premature activation. Here, we report that E‐Cadherin serves that purpose. Having confirmed that cultured mast cells express E‐Cadherin, a mast‐cell‐specific E‐Cadherin deficiency, Mcpt5‐Cre E‐Cdh fl/fl mice, was used to analyze mast cell degranulation in vitro and in vivo. Cultured peritoneal mast cells from Mcpt5‐Cre E‐Cdh fl/fl mice were normal with respect to many parameters but showed much‐enhanced degranulation in three independent assays. Soluble E‐Cadherin reduced the degranulation of control cells. The release of some newly synthesized inflammatory cytokines was decreased by E‐Cadherin deficiency. Compared to controls, Mcpt5‐Cre E‐Cdh fl/fl mice reacted much stronger to IgE‐dependent stimuli, developing anaphylactic shock. We suggest E‐Cadherin‐mediated tissue interactions restrict mast cell degranulation to prevent their precocious activation. Abstract : E‐Cadherin limits IgE‐dependent mast cell degranulation and thus is suggested to contribute to its tissue‐medated control, possibly preventing ohershooting, potentially dangerous immune activation. Mast cell E‐Cadherin deficiency causes enhanced degranulation in vivo and in vitro.